2 answers:
Answer:
a
Step-by-step explanation:
Answer:
![(5, 6)](https://tex.z-dn.net/?f=%285%2C%206%29)
Step-by-step explanation:
<u>Step 1: Solve for x in the first equation
</u>
![x - y + y = -1 + y](https://tex.z-dn.net/?f=x%20-%20y%20%2B%20y%20%3D%20-1%20%2B%20y)
![x = y - 1](https://tex.z-dn.net/?f=x%20%3D%20y%20-%201)
<u>Step 2: Plug in x into the second equation
</u>
![(y - 1) - 3y = -13](https://tex.z-dn.net/?f=%28y%20-%201%29%20-%203y%20%3D%20-13)
![y - 1 - 3y + 1 = -13 + 1](https://tex.z-dn.net/?f=y%20-%201%20-%203y%20%2B%201%20%3D%20-13%20%2B%201)
![-2y / -2 = -12 / -2](https://tex.z-dn.net/?f=-2y%20%2F%20-2%20%3D%20-12%20%2F%20-2)
![y = 6](https://tex.z-dn.net/?f=y%20%3D%206)
<u>Step 3: Plug in y into the first equation
</u>
<u />![x - (6) + 6 = -1 + 6](https://tex.z-dn.net/?f=x%20-%20%286%29%20%2B%206%20%3D%20-1%20%2B%206)
![x = 5](https://tex.z-dn.net/?f=x%20%3D%205)
Answer: ![(5, 6)](https://tex.z-dn.net/?f=%285%2C%206%29)
You might be interested in
Answer:
sub to my you tube channel:
Josiah Rowell
Step-by-step explanation:
-x^3 I think is the answer